Risky sexual behavior and associated factors among patients with bipolar disorders in Ethiopia - Obo, Chalachew Shambel; Sori, Lamesa Melese; Abegaz, Tadesse Melaku; Molla, Bizuneh Tesfaye (BMC psychiatry, 2019)
Background People with bipolar disorder are highly vulnerable to risky sexual behaviors (RSBs). The magnitude of RSBs among bipolar disorders was not studied in our population. The present study aimed to explore the prevalence of RSBs and associated factors among patients with bipolar disorder. Method An institution based cross-sectional study was conducted from 1 April to 30 May 2017 among people living with bipolar disorder at outpatient departments of Amanuel Mental Health Hospital, Addis Ababa. Systematic random sampling was used to select participants. Risky sexual behavior was defined as having sex with two or more sexual partners, having unprotected sexual intercourse, sex after alcohol consumption, exchanged money for sex in a previous 12 months. Data collection was conducted through face-to-face interview by a structured questionnaire adopted from behavioral surveillance survey. Binary logistic regression was conducted to identify factors associated with RSBs. Result A total of 424 participants were enrolled in the study, giving overall response rate of 96%. About 223(52.6%) were males. The prevalence of risky sexual behavior was 49.1% among bipolar patients. Male patients (Adjusted Odds Ratio (AOR) =2.23,95% CI = 1.27,3.92), patients in age group of 18–24(AOR = 2.08,95% CI = 1.47,3.81),current manic phase of the illness (AOR = 2.3195% CI,1.24,4.32) and current alcohol drinking (AOR = 3.70,95% CI = 2.01,6.78) had significant association with RSB. Conclusion Almost half of bipolar patients reported a risky sexual behavior. Current manic episode and the consumption of alcohol were independently associated with RSB. To reduce the burden of RSBs, mental health services which focuses on sexual behaviors of bipolar patients is required.